Improving the Reliability of Tractor Spline Shafts during Heat Treatment (American Journal of Engineering , Mechanics and Architecture (2993-2637), 2023)
When choosing a steel grade, they proceed from general operational, technological and economic requirements. The operational stability of the shafts is determined by fatigue strength, contact strength and corrosion resistance under torsion and fracture conditions. Steel grade 40x, Tractor spline shafts of various diameters during heat treatment with different cooling intensity, quenching is performed on the HDTV unit.